Process Intensification Strategies for the Synthesis of Superparamagnetic Nanoparticles and Fabrication of Nano-Hybrid - Suk, Fun Chin; Iyer, K.S.; Raston, Colin L.; Saunders, Martin (2008)
Superparamagnetic magnetite (Fe3O4) nanoparticles are important for a diverse range of applications such as, magnetic resonance imaging, targeted drug delivery and magnetic separation. The most common cost effective and convenient way to synthesize Fe3O4 nanoparticles is by co-precipitating ferrous and ferric salt solutions with a base, such as aqueous NaOH or NH4OH. However, the size distribution of the Fe3O4 nanoparticles produced using this method is normally very broad. Consequently, the downstream purification and isolation process is more expensive and is time and energy intensive. Furthermore, scale-up of this method using conventional reactors can be problematic given the inhomogeneous agitation and areas of localized pH variations, resulting in the precipitation of non-magnetic iron oxides. Accordingly, there is a growing demand in the nanotechnology industries for processes that promise to make dramatic improvements in the design and performance of the manufacturing equipment involved. The concept of “Process Intensification” offers alternative routes alleviating the obstacles of the relaxed fluid dynamic regime associated with conventional batch processes. Herein we demonstrate the successful synthesis of Fe3O4 nanoparticles via co-precipitation using NH3 gas as a base source using spinning disc processing (SDP) under scalable and continuous flow conditions.